DSB profiles in human spermatozoa highlight the role of TMEJ in the male germline - Scheuren, Maurice; Möhner, Jonas; Müller, Max; Zischler, Hans (Frontiers in Genetics, 2024)
The male mammalian germline is characterized by substantial chromatin remodeling associated with the transition from histones to protamines during spermatogenesis, followed by the reversal to nucleohistones in the male pronucleus preceding the zygotic genome activation. Both transitions are associated with the extensive formation of DNA double-strand breaks (DSBs), requiring an estimated 5 to 10 million transient DSBs per spermatozoa. Additionally, the high transcription rate in early stages of spermatogenesis leads to transcription-coupled damage preceding meiotic homologous recombination, potentially further contributing to the DSB landscape in mature spermatozoa. Once meiosis is completed, spermatozoa remain haploid and therefore cannot rely on error-free homologous recombination, but instead depend on error-prone classical non-homologous end joining (cNHEJ). This DNA damage/repair-scenario is proposed to be one of the main causes of the observed paternal mutation propensity in human evolution. Recent studies have shown that DSBs in the male pronucleus are repaired by maternally provided Polθ in C. elegans through Polθ-mediated end joining (TMEJ). Additionally, population genetic datasets have revealed a preponderance of TMEJ signatures associated with human variation. Since these signatures are the result of the combined effect of TMEJ and DSB formation in spermatozoa and male pronuclei, we used a BLISS-based protocol to analyze recurrent DSBs in mature human sperm heads as a proxy of the male pronucleus before zygotic chromatin remodeling. The DSBs were found to be enriched in (YR)n short tandem repeats and in evolutionarily young SINEs, reminiscent to patterns observed in murine spermatids, indicating evolutionary hotspots of recurrent DSB formation in mammalian spermatozoa. Additionally, we detected a similar DSB pattern in diploid human IMR90 cells when cNHEJ was selectively inhibited, indicating the significant impact of absent cNHEJ on the sperm DSB landscape. Strikingly, regions associated with most retained histones, and therefore less condensed chromatin, were not strongly enriched with recurrent DSBs. In contrast, the fraction of retained H3K27me3 in the mature spermatozoa displayed a strong association with recurrent DSBs. DSBs in H3K27me3 are associated with a preference for TMEJ over cNHEJ during repair. We hypothesize that the retained H3K27me3 may trigger transgenerational DNA repair by priming maternal Polθ to these regions.